Retour sur les lieux de l’evénement : l’image « en creux » - Raphaële Bertho (Images Re-Vues)
It seems an event cannot exist if images of them do not exist. Faced with this excess, this visual “overflowing”, a new posture can be seen in the field of contemporary photography. As “negatives” of the media phenomenon these images evoke major contemporary events by not explicitly representing them. They propose a return to the event, a return to the scene, to try to open a space for reflection on, by, and in the image. The “negation” is not a representation of the absence or disappearance, but of the lack - the lack of visible traces of the event. These works raise the issue of the transmission of experience while uncovering the power of the commonplace in our relationship to the past.